Two chromatographic methods for analyzing paracetamol in spiked human plasma with its toxic metabolite, N-acetyl parabenzoquinone imine and its antidote, N-acetyl-l-cysteine - Omar M El-Abassy; Michael Gamal Fawzy; Ebraam B. Kamel (Scientific Reports)
Abstract Acetaminophen, also known as paracetamol (APAP), is a highly utilized pharmaceutical agent on a global scale, particularly in the field of pediatrics. Regrettably, an overdose of APAP, resulting from the predominant oxidation, has the potential to trigger acute liver injury. The study’s goal was to find an easy, accurate, and selective way to measure APAP, N-acetyl para benzoquinone imine (NAPQI) (an APAP metabolite that is harmful), and N-acetyl-l-cysteine (NAC) (an antidote). Two different chromatographic methods were used. The HPTLC method, which used silica gel 60 F254 as a stationary phase and a developing liquid made up of methanol, ethyl acetate, and glacial acetic acid (8:2:0.2, v/v/v) and a UV detection at 254 nm. The HPLC method was developed using a mobile phase consisting of water, methanol, and formic acid in a proportion of (70:30:0.15, v/v/v). The stationary phase used in the approach was a C18 column. Analytes quantification was established utilizing a UV detector operating at a wavelength of 254 nm. The present methods make it possible to measure the amount of APAP in plasma samples. When it comes to pharmacokinetics or medication levels in children’s plasma, for example, this may be also very helpful. The current methods can quantify NAPQI, which is helpful in figuring out drug concentrations in individuals with APAP intoxication diagnoses. Additionally, the current approaches can estimate NAC as an antidote; as a result, this study is a complete study because it can analyse drug, toxic metabolite, and antidote in one analytical run. Using the innovative blue applicability grade index software, which measures the practicality of procedures, both methodologies were compared with a reported methods. Additionally, the achievement of the eco-friendliness profile of the designed procedures was assessed. Both techniques passed the ICH validation tests.